Pengaruh Media Game Edukasi Teka Teki Pengetahuan Terhadap Minat Belajar Siswa Pada Mata Pelajaran IPA Kelas 5 SDN 03 Protomulyo - Pratami, Wingga (Jurnal Profesi Keguruan, 2017)
This study aims to determine the effect of the use of educational media game "Teka Teki Pengetahuan" to the student's interest in science subjects 5th grade SDN 03 Protomulyo 2016/2017 academic year. Media game education " Teka Teki Pengetahuan" is an interactive multimedia-based media in which to load Materials, and games are made with an attractive design that allows students to understand the learning materials and can increase student learning interest. This study only examines the students' interest in learning. This type of research is a quantitative research in the form of True Experimental Design with Pretest-Posttest Only Control Design design. The sample of this research is 20 students of VA class as experiment class and 20 students of class VB as control class by using technique of non probability sampling in the form of saturated sampling. Data were analyzed using descriptive statistics and one party t test. Based on t test results, it is known that with the significance level ? = 0.05 with tcount = 2.115 and ttable = 2.024. Because> that is 2.115> 2.024 so that H1 is accepted. So it can be concluded that there is a significant influence of educational media media game "Teka Teki Pengetahuan" to the student's interest in science subjects class 5 SDN 03 Protomulyo.